1977
DOI: 10.1001/archpedi.1977.02120150081017
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual and Perceptual-Motor Characteristics of Treated Myelomeningocele Children

Abstract: \s=b\We studied 173 children with myelomeningocele, 133 of whom developed hydrocephalus (and had shunt procedures) and 40 of whom did not. Eighty siblings were tested as a control group. Sixty-three percent of children with hydrocephalus had IQs above 80; 87% of those without hydrocephalus had IQs above 80. Children who had associated hydrocephalus were significantly less intelligent than their siblings, whereas those without hydrocephalus were not. When patients and siblings were matched by age and IQ, the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

1977
1977
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 16 publications
3
33
0
1
Order By: Relevance
“…The mean IQ in our study was similar to results reported by Tew and Laurence 30 and Anderson and Spain, 31 and lower than results from Soare and Raimondi 32 and McLone et al 33 Once again, these discrepancies can be attributed to di erences in criteria (in this case de®nition of IQ) and to the heterogeneity of the samples. Overall distribution of IQ in our series was not gaussian or normal: the distribution curve deviated toward the left.…”
Section: Discussionsupporting
confidence: 87%
“…The mean IQ in our study was similar to results reported by Tew and Laurence 30 and Anderson and Spain, 31 and lower than results from Soare and Raimondi 32 and McLone et al 33 Once again, these discrepancies can be attributed to di erences in criteria (in this case de®nition of IQ) and to the heterogeneity of the samples. Overall distribution of IQ in our series was not gaussian or normal: the distribution curve deviated toward the left.…”
Section: Discussionsupporting
confidence: 87%
“…In a previous study [57] we reported that shunting any time during the first trimester of life was compatible with the attainment of normal psychomo tor function, providing the shunting system was subsequently kept func tioning. We also reported the effects of hydrocephalus in myelomeningo cele children and compared them to their normal siblings and to myelo meningocele children without hydrocephalus, observing that hydrocephal ic myelomeningocele children have significantly lower IQ than nonhydro cephalic myelomeningocele children, but that they do fairly well if the shunts are kept functioning [67], Therefore, we are presently attempting to delay insertion of the initial shunt as much as possible, but never wait ing in newborn with advanced hydrocephalus [54].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of hydrocephalus from different etiologies found lower PIQ than VIQ scores (Dennis et al, 1981;Soare & Raimondi, 1977). Although it is tempting to attribute the PIQ decrement to motor impairment, comparison of the performance of children with SBM on motorbased and motor-free tasks revealed impairment on visiospatial tasks irrespective of the motor requirements .…”
Section: Sbmmentioning
confidence: 97%